2020
DOI: 10.1002/cptc.202000164
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and Characterization of Push‐Pull Aza‐BODIPY Dyes Towards Application in NIR‐II Photothermal Therapy

Abstract: A new series of aza-BODIPYs (CNÀ X) with significantly redshifted absorbances were designed and synthesized by installation of various electron-donating groups on the para-positions of 3,5-phenyl groups while strong electron-withdrawing groups (nitrile groups) were fixed on the para-positions of 1,7-phenyl moieties. Interestingly, strong electron-donating groups such as N'N-dimethylaniline (CNÀ NMe 2) could provide strong NIR absorption up to 857 nm and weak fluorescence emission up to 967 nm, whereas strong e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
23
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 18 publications
(23 citation statements)
references
References 31 publications
0
23
0
Order By: Relevance
“…A previous study by Rattanopas et al compared the effect of electron-donating groups on symmetrical (vertical) push–pull aza-BODIPYs. 17 Having a fixed pull moiety (CN) in the para position of 1,7 phenyls and varying the electron-donating group in the para position of 3,5-phenyls, they observed a transition energy of λ max abs = 853 nm for NMe 2 as the electron-donating moiety. Thus, having the push–pull effect directed vertically shows a greater effect on the transition energy compared to having it directed horizontally.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…A previous study by Rattanopas et al compared the effect of electron-donating groups on symmetrical (vertical) push–pull aza-BODIPYs. 17 Having a fixed pull moiety (CN) in the para position of 1,7 phenyls and varying the electron-donating group in the para position of 3,5-phenyls, they observed a transition energy of λ max abs = 853 nm for NMe 2 as the electron-donating moiety. Thus, having the push–pull effect directed vertically shows a greater effect on the transition energy compared to having it directed horizontally.…”
Section: Resultsmentioning
confidence: 99%
“…The resulting dye class is known as aza-BODIPYs and was discovered in 1943 . Only in the last couple of years, aza-BODIPYs have attracted increasing interest due to their versatility. , This aforementioned small change in the structure can lead to a redshift of about 80 nm, leading to some derivatives absorbing in the red or near-infrared regions of the electromagnetic spectrum. However, a general observation is that aza-BODIPY have lower emission quantum yields compared to BODIPY dyes, , making them less desirable in applications where photons are used as a readout signal. In contrast, they show a higher potential to undergo singlet-to-triplet intersystem crossing, which in combination with their red-shifted absorption leads to new utilizations like photodynamic therapy …”
Section: Introductionmentioning
confidence: 99%
“…A new photosensitizer, aza-BODIPY-A , was synthesized according to a typical aza-BODIPY synthesis, starting from the aldol condensation reaction between acetophenone and benzaldehyde to obtain the corresponding chalcone (Scheme S1). After the addition of nitromethane to the resulting chalcone, the product underwent a coupling reaction to obtain an aza-dipyrromethenes (aza-DIPY), which was then complexed with boron trifluoride etherate (BF 3 ·OEt 2 ) to yield aza-BODIPY-A .…”
Section: Methodsmentioning
confidence: 99%
“…Rattanopas et al synthesized an aza-BODIPY (CN-NMe 2 ) without NIR-II absorption in organic solvents (such as toluene, chloroform, etc.). [47] After encapsulated by bovine serum albumin (BSA), CN-NMe 2 /BSA exhibited broad absorption in the NIR-II region, which could be used for NIR-II PAI-guided NIR-II PTT of tumors. Similar to this, Xiang et al reported a novel small molecule BFF without any absorption in the NIR-II region in tetrahydrofuran.…”
Section: Nir-ii Pai-guided Nir-ii Pttmentioning
confidence: 99%